Understanding deceleration in sport - Hewit, J.; Cronin, J.; Button, C.; Hume, P. (Strength and Conditioning Journal, 2011)
Rapid deceleration is seen in a wide variety of sports when stopping or as a precursor to a change in direction. These rapid changes in velocity often occur over a minimal amount of distance or time and are often in response to external stimuli such as an opponent's movement or boundary lines. Little attention has been given in research literature to the kinematics and kinetics of running deceleration. This article aims to enhance the understanding of the mechanical characteristics associated with deceleration performance.